Motivation and Family Support in Relation to Pregnant Women’s Participation in Prenatal Yoga Classes - Susanti, Silfia Sekar Arum Mandalia Elly; Ekasari, Dily; Garcaia, Zeferina Dos Dantos Noemia; Febriani, Gabriela Advitri; Delpia, Yesi Vila; Uberty, Adhetya (Napande: Jurnal Bidan, 2025)
Background: The adaptation process for a woman during pregnancy is one of the most challenging situations because it involves various discomforts, including back pain, shortness of breath, and anxiety.  One way to address these discomforts is through prenatal yoga. Objective to determine the relationship between motivation and family support on the participation of pregnant women in prenatal yoga classes to reduce discomfort during pregnancy. Method: The study used correlational analytics with a cross-sectional research design. Data were collected from the Independent Midwifery Practice (PMB) Denik between May and June 2025, involving 30 pregnant women selected through total sampling. The research instrument used a questionnaire. Statistical tests used chi-square and logistic regression with an α value (0.05). Results: The study shows that almost all respondents have strong motivation (90.0%), most respondents have sufficient family support (60.0%), and almost all respondents attend yoga classes (90.0%). Logistic regression test p<  (0.001 < 0.05). Conclusion: Maternal motivation is more effective than family support in encouraging  pregnant women to participate in prenatal yoga. Maternal motivation can be used by health workers as a factor to increase participation in prenatal yoga.